Synthesis and characterisation of activated carbon obtained from marula (Sclerocarya birrea) nutshell - Mkungunugwa, Tafadzwa; Manhokwe, Shepherd; Chawafambira, Armistice; Shumba, Munyaradzi (Hindawi, 2022)
Globally, a ninth of people use polluted water sources because an estimated 300–400 Mt of waste and 90% of sewage are discharged into water bodies from industries and developing countries, respectively. The utilisation of indigenous fruit pits in producing novel adsorbents will greatly benefit in wastewater treatment. In most underdeveloped countries, activated carbon (AC) is imported at a high cost. The study was aimed at synthesising and characterisation of AC obtained from Marula nutshell. Carbonization of organic matter from Marula nutshell was carried out at 200°C, 400°C, 500°C, and 600°C. Sulphuric (H2SO4) and phosphoric (H3PO4) acids were used as activating agents at concentrations of 20–60% (v/v). Physicochemical characteristics of the AC, such as bulk density, moisture, ash, pH, and iodine number, were analyzed using standard methods. Functional groups and total carbon content were determined using the FTIR spectroscopy and Nitrogen Carbon Sulphur (NCS) analyzer, respectively. The values of carbon yield and total carbon in activated samples with H2SO4 and H3PO4 were 32.2–93.2%, 26.9–95.8%, and 46–79%, 20.8–69.8%, respectively. The pH, ash, moisture, and bulk density of activated high carbon samples with H2SO4 ranged from 2.4–6.1, 0.65–3.49%, 1.3–8.4%, and 0.42–0.62 gcm−3, respectively. Activated high carbon samples with H3PO4 had 2.7–3.2, 11.3–29.8%, 4.7–14.6%, and 0.39–0.54 gcm−3 pH, ash, moisture, and bulk density, respectively. The synthesised AC samples with 40% H3PO4 at 500°C had the highest iodine value of 1075.7 mg/g. FTIR results showed the presence of aliphatic carboxylic acid salt, inorganic nitrate (NO3−), and phosphate groups in the synthesised AC and were not significantly different (p<0.05) from commercial AC. The untreated Marula nutshell had some aliphatic hydrocarbon (alkanes), inorganic phosphate (PO3-4), aliphatic ester (–COO), and aliphatic carboxylic acid salt (–C(=O)O–) groups. A novel adsorbent, AC was produced from Marula nutshell with the potential to be used in water treatment.